A non‐compulsory stewardship programme for the management of antifungals in a university‐affiliated hospital. (2nd May 2012) - López‐Medrano, F.; San Juan, R.; Lizasoain, M.; Catalán, M.; Ferrari, J. M.; Chaves, F.; Lumbreras, C.; Montejo, J. C.; Herreros de Tejada, A.; Aguado, J. M.
Abstract Antimicrobial stewardship programmes promote excellence in the use of antimicrobials by selecting the appropriate antimicrobial agent and the correct dose, route of administration and duration of treatment. However, there is limited experience with such programmes targeting antifungal treatments. We present the results of a non‐compulsory programme for the control of antifungals. For 12 months, prescriptions of oral voriconazole or intravenous voriconazole, caspofungin and liposomal amphotericin B were reviewed, and non‐compulsory recommendations were made. The incidence and outcome of fungal infections were examined. The results for the dispensed defined daily doses (DDDs) and expenditure on antifungals were compared with those for the previous 12 months. The number of antifungal treatments reviewed was 662. A recommendation to change treatment was made in 29% of the cases, including a change from intravenous to oral treatment (15%), cessation of antifungal treatment (8%), and a change to fluconazole (6%). The DDDs of intravenous voriconazole and caspofungin were reduced by 31.4% and 20.2%, respectively. The DDDs of oral voriconazole and dispensed vials of liposomal amphotericin B were increased by 8.2% and 13.9%, respectively. Expenditure on antifungals was reduced by US370681.78 (11.8% reduction). The programme was not related to significant increases in the incidence of candidaemia, percentage of persistent/relapsing candidaemia cases, percentage of fluconazole‐resistant Candida species, incidence of infections by filamentous fungi, or 12‐month mortality in patients with filamentous fungal infections. In conclusion, a stewardship programme targeting antifungals achieved a reduction in antifungal expenditure without reducing the quality of care provided.